Exosomal circular RNAs: New player in breast cancer progression and therapeutic targets - Hussen, Bashdar Mahmud; Mohamadtahr, Sayran; Abdullah, Snur Rasool; Hidayat, Hazha Jamal; Rasul, Mohammad Fatih; Hama Faraj, Goran Sedeeq; Ghafouri-Fard, Soudeh; Taheri, Mohammad; Khayamzadeh, Maryam; Jamali, Elena (Frontiers in Genetics, 2023)
Breast cancer is the most prevalent type of malignancy among women. Exosomes are extracellular vesicles of cell membrane origin that are released via exocytosis. Their cargo contains lipids, proteins, DNA, and different forms of RNA, including circular RNAs. Circular RNAs are new class of non-coding RNAs with a closed-loop shape involved in several types of cancer, including breast cancer. Exosomes contained a lot of circRNAs which are called exosomal circRNAs. By interfering with several biological pathways, exosomal circRNAs can have either a proliferative or suppressive role in cancer. The involvement of exosomal circRNAs in breast cancer has been studied with consideration to tumor development and progression as well as its effects on therapeutic resistance. However, its exact mechanism is still unclear, and there have not been available clinical implications of exo-circRNAs in breast cancer. Here, we highlight the role of exosomal circRNAs in breast cancer progression and to highlight the most recent development and potential of circRNA as therapeutic targets and diagnostics for breast cancer.